The Effect of Internal Control, Human Resources and Utilization of Accounting Information Technology on the Quality of Financial Statements of Savings and Loans Cooperatives in Rembang Regency - Sulasmining Sulasmining; Siti Alliyah (Lembaga Riset dan Inovasi Al-Matani, 2023)
The purpose of this study was to determine the effect of internal control, human resources and the use of accounting information technology on the quality of savings and loan cooperative financial reports. This study used a purposive sampling technique so that a sample of 33 savings cooperatives in Rembang Regency was obtained. Methods of data collection using questionnaires. The data analysis technique used multiple linear regression analysis using SPSS 23. The results showed that partially the influence of internal control, human resources and the use of accounting information technology had a significant effect on the quality of financial statements of savings and loan cooperatives.